2020
DOI: 10.1002/cncr.32624
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world use and survival outcomes of immune checkpoint inhibitors in older adults with non–small cell lung cancer

Abstract: Background Limited data exist regarding the characteristics and survival outcomes of older adults with non–small cell lung cancer (NSCLC) who receive immune checkpoint inhibitors in routine oncology practice. Methods Using the Surveillance, Epidemiology, and End Results–Medicare linked database, we identified 1256 patients aged ≥65 years who were diagnosed with pathologically confirmed stage I to stage IV NSCLC between 2002 and 2015 and initiated nivolumab or pembrolizumab in 2016. We examined patient characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 21 publications
5
61
2
Order By: Relevance
“…Except for adenocarcinomas and squamous cell histology of lung cancer, most variables demonstrate significant negative OS in the NSCLC immunotherapy era. In addition, aging is significantly linked to negative OS in patients with NSCLC who died from heart diseases; this finding was also recently shown in a SEER-Medicare study by Bora et al, who report that comorbidities and negative OS are related to old age in NSCLC patients who were started with immune checkpoint inhibitors (18). Recently, several reports indicate that the combining of chemoradiotherapy with immunotherapy has superior efficacy in producing improved anticancer activity (19).…”
Section: Discussionmentioning
confidence: 64%
“…Except for adenocarcinomas and squamous cell histology of lung cancer, most variables demonstrate significant negative OS in the NSCLC immunotherapy era. In addition, aging is significantly linked to negative OS in patients with NSCLC who died from heart diseases; this finding was also recently shown in a SEER-Medicare study by Bora et al, who report that comorbidities and negative OS are related to old age in NSCLC patients who were started with immune checkpoint inhibitors (18). Recently, several reports indicate that the combining of chemoradiotherapy with immunotherapy has superior efficacy in producing improved anticancer activity (19).…”
Section: Discussionmentioning
confidence: 64%
“…LUSC and LUAD are the two major subtypes of lung cancer, in which LUSC progresses faster than LUAD of the same stage [28]. Tumor-related prognosis or predictive markers in the immune microenvironment significantly changed the treatment prospects of lung cancer and significantly improved the prognosis of some patients, especially those with adenocarcinoma [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Using the SEER-Medicare database, Youn et al [38] identified 1256 patients aged ≥65 years who had NSCLC between 2002 and 2015 and initiated nivolumab or pembrolizumab in 2016. These patients had stage I (n = 229), stage II (n = 75), stage III (n = 417), or stage IV (n = 535) cancer and had received no previous systemic therapy (n = 102).…”
Section: Efficacy Of Icis For Elderly Nsclc Patients In Non-randomizementioning
confidence: 99%